2021
DOI: 10.1017/s1744137420000624
|View full text |Cite
|
Sign up to set email alerts
|

Resilience to economic shrinking in an emerging economy: the role of social capabilities in Indonesia, 1950–2015

Abstract: Economic history has recently emphasised the impact of economic shrinking on long-term economic growth, but economic theories do not provide explanations for how and why some countries avoid economic shrinking. In this case study of institutional change in post-independence Indonesia, we examine how the country managed to reduce the frequency of shrinking during the authoritarian regime and beyond. We argue that the state's autonomy, measured by macroeconomic policymaking, and accountability, measured by food … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(28 citation statements)
references
References 51 publications
1
27
0
Order By: Relevance
“…These results sail together with research that revealed cultural and institutional aspects that made it easy to understand human behavior, individual choices, and patterns of society (Andriani &Bruno, 2021). Human behavior is driven by socio-cultural norms, including the principle of social interaction "tuna satak bathi sanak" might be a survival strategy, despite institutional constraints and economic sanctions in various socio-economic contexts (Prasetyo, 2020e;Andriani & Bruno, 2021;Andersson et al, 2021). Meanwhile, Andersson et al (2021) stated that economic development in Indonesia includes a process through socio-cultural capabilities and is not limited to the role of state institutions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results sail together with research that revealed cultural and institutional aspects that made it easy to understand human behavior, individual choices, and patterns of society (Andriani &Bruno, 2021). Human behavior is driven by socio-cultural norms, including the principle of social interaction "tuna satak bathi sanak" might be a survival strategy, despite institutional constraints and economic sanctions in various socio-economic contexts (Prasetyo, 2020e;Andriani & Bruno, 2021;Andersson et al, 2021). Meanwhile, Andersson et al (2021) stated that economic development in Indonesia includes a process through socio-cultural capabilities and is not limited to the role of state institutions.…”
Section: Resultsmentioning
confidence: 99%
“…Human behavior is driven by socio-cultural norms, including the principle of social interaction "tuna satak bathi sanak" might be a survival strategy, despite institutional constraints and economic sanctions in various socio-economic contexts (Prasetyo, 2020e;Andriani & Bruno, 2021;Andersson et al, 2021). Meanwhile, Andersson et al (2021) stated that economic development in Indonesia includes a process through socio-cultural capabilities and is not limited to the role of state institutions. This means that the pattern of human cultural behavior that is uncorrupt and applicable norms has helped eliminate institutional barriers.…”
Section: Resultsmentioning
confidence: 99%
“…The aim of the analytic narrative approach is to use thick descriptions analysed through an elaborate analytical framework to increase the understanding of Ethiopia's past and present growth experience. This approach is similar to that of Rodrik (2003) and Andersson et al (2021) and is directly inspired by Andersson With these methods, the paper studies social capability over time rather than across space or compared to a benchmark level of social capability derived from previous growth experiences. Therefore, the analysis focuses on whether the elements of social capability are strengthening or weakening, not whether they are high or low.…”
Section: Methodsmentioning
confidence: 99%
“…The last two elements of the social capability framework are intended to capture the presence of effective political institutions in Ethiopia. Following Andersson et al (2021), state autonomy is seen as the state's ability to avoid being captured by vested interests and to maintain sound macroeconomic policies without wavering in the face of populist pressure. Following Evans's (1995) understanding of 'embedded autonomy ' and Fukuyama's (2013) observation that a state's fiscal capacity is a key element of state autonomy, three indicators are used to empirically capture the extent of state autonomy: the extent of taxation, inflation and the ability to balance the budget.…”
Section: Analytical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation